Integrated watershed management: a review - Belay Zerga (Discover Sustainability)
Abstract The area of land and water that contributes runoff to a common point is known as the watershed. Recognizing watersheds as dynamic systems with intricate interactions among land, water, and biota, the notion of watershed management entails a comprehensive and integrated approach to resource stewardship. The opportunity provided by watershed management is to comprehend and balance the relationships between different land use systems. Watershed management represents a crucial nexus between environmental conservation and sustainable development, addressing the complex interplay of ecological, social, and economic factors within a defined geographical area. The objective of this review study was to evaluate integrated watershed management’s significance on a worldwide level and to assess components such as soil and water conservation, plantation, agronomic practices, livestock management, renewable energy policy and legal frameworks, and case studies. In this review systematic method was used. After choosing a research topic, relevant publications were found and downloaded from several research databases, such as Scopus, Web of Science, and Google Scholar. Four inclusion and exclusion criteria were applied. According to the review's findings, the most effective ways to address watershed degradation in both rich and developing nations are biological and engineering solutions. The most suitable way to describe this is that integrated watershed management activities seemed to have increased household income, increased plant cover, and decreased soil erosion. A set of policies, guidelines and legal frameworks for managing watersheds must guarantee the conservation and sustainable use of natural resources within their boundaries. By incorporating ecological, social, and economic factors into watershed management techniques, these principles will offer a framework for fostering environmental integrity, equity, and resilience.